Effect of frost heave on long-term roughness deterioration of flexible pavement structures. Issue Volume 20:Issued 6(2019) (3rd June 2019) - Sylvestre, Olivier; Bilodeau, Jean-Pascal; Doré, Guy
ABSTRACT: In northern regions, the frost heave of the subgrade soils due to formation of ice lens is the main mechanism involved in the high degradation rate of the flexible pavement. This paper presents developments of flexible pavement damage models, developed through a multiple linear regression analysis, associated long-term roughness performance to frost heave and degradation mechanisms. Actually, there is no deterioration model that establishes a link between frost heave and flexible pavement. At a design stage, those models would be essential to evaluate the benefits or consequences to have a frost heave lower, equal or higher than the allowable threshold values established by the MTMDET according to the roads functional classification. The result presented illustrate that a significant increase in long-term IRI deterioration rate, usually caused by a more variable subgrade soil, is likely to contribute to the rehabilitation of the pavements up to four years before the end of the pavement service life. This project will allow the administration and the builders to adapt the construction of road infrastructures in cold regions in order to achieve the objectives established to maintain the safety of the users.